2022
DOI: 10.1016/j.gim.2021.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Phase 3 trial of lumasiran for primary hyperoxaluria type 1: A new RNAi therapeutic in infants and young children

Abstract: Primary hyperoxaluria type 1 (PH1) is a rare, progressive, genetic disease with limited treatment options. We report the efficacy and safety of lumasiran, an RNA interference therapeutic, in infants and young children with PH1. Methods: This single-arm, open-label, phase 3 study evaluated lumasiran in patients aged <6 years with PH1 and an estimated glomerular filtration rate >45 mL/min/1.73 m 2 , if aged ≥12 months, or normal serum creatinine, if aged <12 months. The primary end point was percent change in sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
71
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(78 citation statements)
references
References 29 publications
6
71
0
1
Order By: Relevance
“…Lumasiran demonstrated an acceptable safety profile in the 6-month primary analysis period of ILLUMINATE-C. Consistent with what was previously reported in patients with preserved kidney function, 19,20 the most common AEs related to lumasiran treatment were injection-site reactions, all of which were mild and transient.…”
Section: Illuminate-c Evaluated the Efficacy And Safety Of Lumasiran ...supporting
confidence: 83%
See 3 more Smart Citations
“…Lumasiran demonstrated an acceptable safety profile in the 6-month primary analysis period of ILLUMINATE-C. Consistent with what was previously reported in patients with preserved kidney function, 19,20 the most common AEs related to lumasiran treatment were injection-site reactions, all of which were mild and transient.…”
Section: Illuminate-c Evaluated the Efficacy And Safety Of Lumasiran ...supporting
confidence: 83%
“…24,[27][28][29] In previous studies, treatment with lumasiran was shown to achieve substantial and sustained reductions in UOx with an acceptable safety profile in patients with relatively J o u r n a l P r e -p r o o f preserved kidney function. 19,20 Treatment with lumasiran also led to rapid and sustained reductions in UOx in Cohort A in ILLUMINATE-C. As expected, anuria in Cohort B was nearly universal, precluding meaningful analysis of UOx. The post-baseline increase in plasma glycolate observed in ILLUMINATE-C was consistent with the mechanism of action of lumasiran and with previous findings in patients with relatively preserved kidney function, 19,20 suggesting comparable liver uptake of lumasiran and target suppression with the recommended weight-based dosing regimen in patients with advanced PH1.…”
Section: Illuminate-c Evaluated the Efficacy And Safety Of Lumasiran ...mentioning
confidence: 53%
See 2 more Smart Citations
“…A double-blinded randomized trial in PH1 patients aged six years or older has demonstrated a 53.5% reduction in 24-hour urinary oxalate excretion and a substantial decrease in plasma oxalate levels [4]. An open-label trial of patients <6 years with PH1 has demonstrated a 72% reduction in spot urine oxalatecreatinine ratio [6].…”
Section: Introductionmentioning
confidence: 99%